Assessment Of Depression Among Medical Students of Private University in Bhopal, India - Sharma, Anshuman; Gupta, Sanjay Kumar; Khare, Neeraj; Agarwal, Sanjay S (National Journal of Community Medicine, 2015)
Introduction: Medical students repeatedly experience different stresses which render them more vulnerable to psychological problems that may affect their emotional, psychosocial and phys- ical health. Objectives of the study were to determine the preva- lence of depression and associated factors leading to depression among medical students at People’s University. Method: This was a cross-sectional study conducted in Peoples University using Theoretical Depressive Experiences Question- naire (TDEQ) there were 440 students participated in the study with duration of 1 month. Results: The participation rate was 90% (396 students). The mean age of participants was 21 ± 2 years, and more than half (62% i.e. 246 students) were males. The prevalence of depression among students was 31 % (123 students). Conclusions: Symptoms of moderate severity were the predomi- nant among students with the studied psychological illnesses. A substantial proportion of medical students had ongoing psychiat- ric problems that were associated with multiple social, behav- ioural, and educational factors. Interventions addressing the mental health of medical students should be initiated.